Solution of the Multigroup Neutron Diffusion Eigenvalue Problem in Slab Geometry by Modified Power Method - Rodrigo Zanette; Claudio Zen Petersen; Matheus Gularte Tavares (Brazilian Journal of Radiation Sciences)
We describe in this work the application of the modified power method for solve the multigroup neutron diffusion eigenvalue problem in slab geometry considering two-dimensions for nuclear reactor global calculations. It is well known that criticality calculations can often be best approached by solving eigenvalue problems. The criticality in nuclear reactors physics plays a relevant role since establishes the ratio between the numbers of neutrons generated in successive fission reactions. In order to solve the eigenvalue problem, a modified power method is used to obtain the dominant eigenvalue (effective multiplication factor) and its corresponding eigenfunction (scalar neutron flux), which is non-negative in every domain, that is, physically relevant. The innovation of this work is solving the neutron diffusion equation in analytical form for each new iteration of the power method. For solve this problem we propose to apply the Finite Fourier Sine Transform on one of the variables obtaining a transformed problem which is resolved by well-established methods for ordinary differential equations. The inverse Fourier Transform is used to reconstruct the solution for the original problem. It is known that the power method is an iterative source method in which is updated by the neutron flux expression of previous iteration.  Thus, for each new iteration, the neutron flux expression becomes larger and more complex due to analytical solution what makes us propose that it be reconstructed through a polynomial interpolation. The methodology is implemented to solve a homogeneous problem and the results are compared with works presents in the literature.